Development of stretchable and bendable polymer wearable antenna for 5G applications - Shakhirul Mat Salleh; Mohd Fadzil Ain; Zulkifli Ahmad; Intan Sorfina Zainal Abidin; Che Muhammad Nor Che Isa (eXPRESS Polymer Letters)
Smart polymer nanocomposite (SPN) is a major interest in the development of wearable electronics, which requires the conductive matrix to be both flexible and stretchable. Polydimethylsiloxane (PDMS) was chosen in this study as it offers flexibility, thermal stability, relative isotropic, homogeneity, low permittivity, and ease of fabrication. The conductive silver paste filler loadings of 40, 50, 60, and 65 wt% were constructed and measured, which showed high conductivity in the range of 1.59–6.58・106 S/m. A rectangular microstrip patch antenna was fabricated based on stretchable PDMS substrate and silver paste polysiloxane composite at a resonance frequency of 3.5 GHz for fifth-generation (5G) communication. The proposed antenna was designed to attach to the human body and integrate with a wearable device. The polymer wearable antenna will easily stretch and bend following the human body shape and movements, which was investigated to further understand the antenna performance at different stretching and bending conditions. Furthermore, the specific absorption rate (SAR) wearable antenna was analysed for safety purposes.